Hedging in the discussion sections of English and Malay educational research articles - Chek, Kim Loi; Lim, Jason Miin-Hwa (Penerbit Universiti Kebangsaan Malaysia, 2019)
Academic writers resort to hedging as one of the interpersonal metadiscourse categories needed to present their findings cautiously in the hope that their research contribution can be accepted by the academic community. Such acceptance, to a great extent, depends on how propositions and claims are presented to the academic community. The purpose of the present study was to compare and contrast the hedges used in the Discussion sections of educational research articles in English with those in Malay. To provide additional insights, information was elicited from both English and Malay specialist informants on their perceptions of hedging in research article writing. This study contributes to an understanding on the use of hedges throughout the Discussion sections of the research articles from the two languages and possible contextual and socio-cultural factors which may have influenced their use. The corpus of the present study is made up of the Discussion sections of English and Malay research articles published between 2012 and 2017. The analytical framework of this study is based on Hyland’s (1996) four hedging functions, which are writer-oriented, attributeoriented, reliability-oriented, and reader-oriented. Our analysis shows that overall, hedges are found in more English than Malay discussions. The greater number of hedges in the English data is in principle expected as English is a remarkably hedging culture. A closer examination reveals that English writers tend to subtly bring the value of the writer’s contribution to the fore, tone down the force of the arguments, and bring forth the tentative nature of the conclusion drawn on the issue examined. The findings provide pedagogical implications in an English for Academic Purposes (EAP) classroom.